MISOGYNY IN MARGARET ATWOOD’S SURFACING - Pramesti, Tri; Supsiadji, Mateus Rudi (BASIS (Bahasa dan Sastra Inggris), 2022)
The aimed of this study is to show misogyny exposed by male character in Margaret Atwood’s  Surfacing.  Margaret Atwood unveils patriarchal practice in a seemingly perfect marriage.  Surfacing tells the story of the wife who lives under the pressure of her husband. Using feminist literary approach, this novel is scrutinized by applying close reading method. The source of data for this study is Surfacing  the novel, book reviews, and articles written by and about author of the book. This is a textual study, in collecting the data, the researchers applied the data gathered in the form of words, phrase and sentence Some steps are taken in collecting the data, the first step is reading and understanding the theme, character, and the backdrop of the story. The next step is Identifying the words, quotations, and dialogs relating to the theme. The data are analyzed descriptively.  Based on the analysis, misogyny exposed in this novel is embedded in a culture and internalized the customs. The inferior position of woman is a result of male domination in all aspects of life.  It is concluded that woman is oppressed economically, traditionally and ideologically. Patriarchal ideology exposed in this novel shows that wife/woman is like goods that which can be treated according to the wishes of the husband/owner.